2015
DOI: 10.1089/jwh.2014.4930
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with a Lack of Pap Smear Utilization in Women Exposed In Utero to Diethylstilbestrol

Abstract: Background: Women in the1940s-1960s were prescribed diethylstilbestrol (DES), a nonsteroidal estrogen, to prevent miscarriages, but the practice was terminated after it was discovered that the daughters so exposed in utero were at increased risk for developing clear cell adenocarcinoma (CCA) of the vagina or cervix at early ages. Pap smear screening is one of the principal methods used to identify tumor development and is necessary in this group of women to maintain their health. Currently, little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…That might mean that we could miss patients with a clear cell adenocarcinoma of the cervix as there is no correlation with HPV. There is currently no screening for in utero DES exposure for women, although they belong in a high-risk group [ 17 ]. In research papers investigating the correlation of in utero des exposure with cervical cancer, there is a higher documented risk for CIN2+.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That might mean that we could miss patients with a clear cell adenocarcinoma of the cervix as there is no correlation with HPV. There is currently no screening for in utero DES exposure for women, although they belong in a high-risk group [ 17 ]. In research papers investigating the correlation of in utero des exposure with cervical cancer, there is a higher documented risk for CIN2+.…”
Section: Discussionmentioning
confidence: 99%
“…A study in France also suggested annual screening of cervix and vagina for these women and that it continues beyond 65-years of age and after hysterectomy with cytological examination [ 19 ]. We would need to tailor the screening program and identify those few individuals with DES exposure to aid in the early detection of cervical and vaginal adenocarcinomas [ 17 ]. Recurrence of CCAC has been reported as long as 20 years after primary therapy, emphasizing the importance of prolonging follow up.…”
Section: Discussionmentioning
confidence: 99%